Fusicoccum rot in mangoes submitted to low doses of gamma irradiation - Santos, Alice Maria Gonçalves; Oliveira, Sônia Maria Alves de; Silva, Josenilda Maria da; Terao, Daniel (Pesquisa Agropecuaria Brasileira, 2011)
This study aimed to evaluate the effect of gamma irradiation in low doses on the postharvest control of 'Tommy Atkins' mango rot caused by Fusicoccum, and to evaluate the effect of this method on the physicochemical characteristics of the fruit. Fruits in ripening stage 1,5 and apparently free of disease were inoculated with 10 μL of a Fusicoccum parvum suspension at 106 conidia mL-1. They were gamma irradiated with the doses 0.24, 0.35 and 0.45 kGy, and stored under 13°C for 15 days, followed by a further six days at room temperature, 25°C. The higher dose of gamma radiation was effective in delaying the disease development due to fruit delayed maturation. No significant effect of radiation was observed on fruit physicochemical characteristics. Fruit maintained ideal commercialization features even after cold storage, in the presence of plastic film, for 15 days.